Australian Thripinae of the Anaphothrips genus-group (Thysanoptera), with three new genera and thirty-three new species - Mound, Laurence A.; Masumoto, Masami (Zootaxa, 2009)
Relationships are considered among taxa of Thripinae lacking long setae on the pronotum, and these taxa are here discussed as the Anaphothrips genus-group. Seven genera from Australia are considered members of this group: Anaphothrips, Apterothrips, Aptinothrips, Caprithrips, Dodonaeathrips gen.n., Ozanaphothrips gen. n. and Pandorathrips gen. n. Six new species are described in Ozanaphothrips, and one each in Dodonaeathrips and Pandorathrips. The worldwide genus Anaphothrips now comprises 79 species, of which 43 are here recorded from Australia, including 27 new species. In other parts of the world Anaphothrips species breed on grasses, but hostassociations of the Australian species are remarkably diverse, involving at least 20 plant families. Illustrated keys are provided for the identification of the Anaphothrips genus-group taxa from Australia. Variation is discussed in the form of the pore plates (=glandular areas or areae porosae) that occur on the sternites of males.